A STUDY OF L2 LEARNERS’ METAPHORICAL COMPETENCE AND PERSONALITY TYPES: A CASE OF THINKING/FEELING VS. JUDGING/PERCEIVING PERSONALITY CATEGORIES - Mahmood Hashemian (Indonesian Journal of Learning and Instruction)
This study explores the (possible) relationship between affective variables and metaphorical competence. The main objective is to investigate the difference between the thinking/feeling and the judging/perceiving personality variables and L2 learners’ metaphorical competence. Participants are 90 male and female Iranian L2 learners who take the OPT and responded to the Myers Briggs Type Indicator (MBTI) personality questionnaire. They are divided into 2 categories of thinking/feeling and judging/perceiving in line with the results of the MBTI. Then, a teacher-made metaphor test is administered to the groups to check their metaphorical competence. Finally, to observe whether there is any significant difference between the 2 groups in terms of metaphor comprehension, an independent samples t test is carried out. The metaphor test is the dependent variable and the personality type is the independent variable. Results show that the thinking/feeling personality category has no significant effect on the participants’ metaphorical competence, whereas the judging/perceiving personality category play some role in their metaphorical competence in that the perceiving participants outperformed the judging ones on the metaphor test.